Analyzing the Impact of Ecotheatre on Public Awareness and Behavior Change - Saaduddin, Saaduddin; Yuda, Faridho; Ramadhan, Alfian; Fadjri, Ahmad Ridwan; Finolia, Lingga; Listiani, Kiki (Pascasarjana Institut Seni Indonesia Padang Panjang, 2024)
Menganalisis Dampak Teater Ekologi terhadap Kesadaran Publik dan Perubahan PerilakuThis study aims to explore the role of ecotheatre in raising environmental awareness and promoting behavior change through a case study of the theatrical performance